Utilization of Pumpkin seed waste extract as an inhibitor in reducing the corrosion rate on metals - Syarif Hidayatullah; Nasmi Herlina Sari; Ahmad Akromul Huda; Maharsa Pradityatama; Sinarep Sinarep; suteja suteja (Protech Biosystems Journal, 2025)
Our research focuses on enhancing the potential of pumpkin seed waste extract as a sustainable corrosion inhibitor for metal (Fe) in 1 M HCl solution. Phytochemical screening and antioxidant activity were identified. Various investigative methodologies including experimental techniques such as Potentiodynamic Polarization (PDP) were used to evaluate the effectiveness of these pumpkin seed waste extract inhibitors in inhibiting corrosion. Electrochemical results showed that the effectiveness of the inhibitor was concentration dependent here reaching 83.11% at 3000 g/L pumpkin seed waste extract inhibitor. The PDP showed that the mixed inhibition control effectively retarded the corrosion of the metal. Furthermore, the adsorption behavior of the pumpkin seed waste extract inhibitor onto the metal follows the Langmuir isotherm model with physisorption properties. The adsorption mechanism of the inhibitor on the metal surface successfully formed a protective film on the metal surface thereby reducing the corrosion rate.